Analisis Faktor-Faktor yang Mempengaruhi Tax Avoidance - Desi Handayani; Olivia Gestri Sani; Zahara Zahara (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2026)
This study aims to examine the effect of related party transactions, sales growth, and capital intensity on tax avoidance in manufacturing companies during the 2020–2024 period. Tax avoidance has become an important issue since, it potentially reduces state revenue and creates conflicts of interest between management as agents and shareholders as well as the government as principals, as explained by agency theory. This research employs a quantitative approach using secondary data in the form of annual financial reports obtained from the official IDX website. The sample was selected using a purposive sampling method based on specific criteria, resulting in 47 companies as the research sample. Data were analyzed using panel data regression. The results show that simultaneously, related party transactions, sales growth, and capital intensity affect tax avoidance. However, partially, only related party transactions and capital intensity are proven to have a significant effect, while sales growth does not have a significant effect. These findings indicate that tax avoidance practices are more closely related to corporate strategies in managing related party transactions and fixed asset investments rather than sales growth. This study is expected to provide theoretical contributions by enriching the literature on the determinants of tax avoidance and practical contributions for companies, regulators, and future researchers in formulating tax policies and more effective supervision strategies.